Buckminsterfullerene C60: A chemical Faraday cage for atomic nitrogen - Pietzak, Björn; Waiblinger, M.; Almeida Murphy, T.; Weidinger, Alois; Hohne, M.; Dietel, Elke; Hirsch, Andreas (Chemical Physics Letters, 1997)
N@C (atomic nitrogen in C, produced by ion implantation) is the first member of a new class of endohedral fullerenes in which a highly reactive atom in its atomic ground state is enclosed in C. Nitrogen in C is chemically inert and stable under ambient conditions. The atomic states of nitrogen in C can be slightly tuned by cage distortions caused by exohedral additions to N@C. In this Letter, a new and simple production method for N@C is described and the effect of cage distortions on the atomic states of nitrogen is discussed. © 1997 Elsevier Science B.V.